Price Volatility, Trading Volume, and Market Depth: Evidence from Futures Markets - Bessembinder, Hendrik; Seguin, Paul J. (Journal of Financial and Quantitative Analysis, 1993)
Hendrik Bessembinder, Paul J. Seguin, Price Volatility, Trading Volume, and Market Depth: Evidence from Futures Markets, The Journal of Financial and Quantitative Analysis, Vol. 28, No. 1 (Mar., 1993), pp. 21-39